Mathematical modeling and validation of solar-induced ventilation system for vehicle cabin cooling in hot parking conditions - Lahimer, A. A.; Amir, Abdul Razak; Kamaruzzaman, Sopian (Akademi Baru, 2023)
Exposure to direct sunlight raises interior temperatures in vehicle cabins, risking heat-related illnesses. Solar passive techniques mitigate this issue, especially during hot parking conditions. However, a comprehensive mathematical model encompassing both solar chimney and vehicle cabin is lacking. This study develops a novel mathematical model to predict temperature distribution and airflow rate, enhancing system performance evaluation. The system comprises a solar air collector with an adjustable arm mounted on the vehicle's roof. The model was validated theoretically and experimentally. The experimental work is conducted with the physical model with an air gap of 0.1 m, 0.77 m width, and a 1.12 m collector length underoutdoor conditions. Results indicated a gradual increase in temperatures of the glass cover, air in the collector channel, absorber, and mass airflow rate with solar radiation intensity, significantly influencing system performance. The high value of R2 and the consistency of the model's results with theoretical and experimental outcomes justified the validity and accuracy of the proposed model, exhibiting a deviation percentage of less than 10%. The developed model can be utilized to study influential parameters for optimizing the proposed strategy's performance and components, yielding comparable results to experimental data. Additionally, it provides researchers and car makers with a broader perspective and a range of options for further improvement in weight, size, cost, and aerodynamic of the vehicle